2022
DOI: 10.3390/brainsci12121685
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Endonasal Skull Base Surgery Complication Avoidance: A Contemporary Review

Abstract: The endoscopic endonasal approach (EEA) provides a direct trajectory to ventral skull base lesions, avoidance of brain retraction, and clear visualization of cranial nerves as they exit skull base foramina. Despite these benefits, the EEA is not without complications. Here, we review published literature highlighting complications associated with the EEA including cerebrospinal fluid (CSF) leak, cranial nerve (CN) dysfunction, pituitary gland dysfunction, internal carotid artery (ICA) injury, infection, and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 177 publications
0
7
0
Order By: Relevance
“…EES surgeons must use tactile feedback from their surgical instruments and sustain a high level of focus to maintain anatomic orientation given substantial interpatient variability in anatomy . Failure to maintain anatomic orientation can be associated with injury to intracranial, vascular, and orbital structures with substantial patient morbidity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EES surgeons must use tactile feedback from their surgical instruments and sustain a high level of focus to maintain anatomic orientation given substantial interpatient variability in anatomy . Failure to maintain anatomic orientation can be associated with injury to intracranial, vascular, and orbital structures with substantial patient morbidity …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Failure to maintain anatomic orientation can be associated with injury to intracranial, vascular, and orbital structures with substantial patient morbidity. [8][9][10] Image guidance is used by most sinus and skull base surgeons. 1,11 These surgical navigation systems, which align medical imaging with intraoperative patient anatomy, have been endorsed by the American Academy of Otolaryngology-Head & Neck Surgery and American Rhinologic Society as adjunct resources for surgical decision-making.…”
mentioning
confidence: 99%
“…An understanding of nasal and paranasal sinus anatomy is of paramount importance for both neurosurgeons and otolaryngologists in the endonasal approach to skull base pathologies. Endoscopic endonasal approaches were traditionally confined to paranasal sinus operations and pituitary adenomas [ 1 ]; however, with significant advances in technology, instrumentation, reconstruction, and the development of novel corridors over the past decade, the endonasal approach to the skull base is now able to safely access pathologies from the frontal sinus to the craniocervical junction in the sagittal plane, the petrous apex in the coronal plane, and posteriorly to the clivus and posterior cranial fossa [ 1 , 2 , 3 , 4 , 5 ]. Congenital lesions include nasal glial heterotopia, seromucinous hamartomas, encephalocele, inflammatory pseudotumor, sinonasal papilloma, polyps, and pituitary adenomas.…”
Section: Introductionmentioning
confidence: 99%
“…Also, anterior and posterior ethmoidal arteries are important anatomic structures to be identified, especially in revision surgery where protective bone in these regions may have been removed. Moreover, gadolinium-enhanced images are valuable in identifying dural enhancement and parenchymal extension 2 .…”
mentioning
confidence: 99%
“…To avoid ICA injury, the surgeon should always enlarge the opening in an infero-medial direction, should not use instrumentation within the sinus cavity and not remove the intersphenoid septum. Recent studies showed that the micro-Doppler ultrasound and neuronavigation might decrease the rates of ICA injuries 2 .…”
mentioning
confidence: 99%